Analisis Perbandingan Produktivitas dan Tingkat Keuntungan Usahatani Ubi Jalar Cilembu - Tito Hardiyanto; Cecep Pardani; Kelik Putranto; Mirna Rianti Setiawati (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2026)
Sumedang Regency is known for its leading commodity, Cilembu sweet potato. This study aimed to analyze the competitive advantage and farming efficiency of Cilembu sweet potato farming in Sumedang Regency. The research used a quantitative approach by comparing farming productivity and R/C ratio values in two production centers, namely Pamulihan and Tanjungsari Districts. Data were collected through surveys using questionnaires distributed to 124 farmers selected through simple random sampling. Data analysis was conducted using productivity and R/C ratio approaches to determine competitive advantage and farming efficiency. The results showed that Cilembu sweet potato farmers were generally of productive age, had moderate education levels, and possessed sufficient farming experience to support farming activities. Farming in both districts was considered feasible, with production costs dominated by labor and fertilizer expenses. However, Pamulihan District demonstrated higher productivity, income, and R/C ratio (1.91) compared to Tanjungsari, indicating better competitive advantage and competitiveness. Meanwhile, Tanjungsari needs improvements in productivity, cost efficiency, and selling prices to enhance its competitiveness.